Pengaruh Implementasi Nearpod sebagai Alat Evaluasi pada Pembelajaran dalam Jaringan terhadap Hasil Belajar Kognitif - Fajri, Muhammad; Sutarjo, Ajo; Hanif, Muhammad (Didaktika, 2022)
Implementation of a learning platform that provides digital evaluation features is urgently needed at this time, one of them is Nearpod which provides a digital learning outcome evaluation feature but can provide fun for students. Generally, teachers still do some evaluations in the old way that uses paper and pencil. Even though implementation of digital evaluation will give teachers a lot of profit. The purpose of this research is to determine student cognitive learning outcomes with the implementation of Nearpod as an evaluation tool. The type of research is experimental research with true experimental design. Based on the results of the independent sample t-test, the results showed that there is a significant difference based on the post-test between an experimental class that uses Nearpod and a control class that uses conventional evaluation tools. Besides that, there is a difference between the results of the independent sample t-test on the pre-test and the results of the independent sample t-test on the post-test, this indicates a difference after the implementation of Nearpod as an evaluation tool in the experimental class. This research also shows that there is an increase in average cognitive learning outcomes of experimental classes from 55.56 to 79.52. Based on the results of the research, can be concluded that cognitive learning outcomes with the implementation of Nearpod as an evaluation tool in fifth-grade elementary school students have increased significantly.